2009
DOI: 10.1037/a0015546
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national variation in the size of sex differences in values: Effects of gender equality.

Abstract: How does gender equality relate to men's and women's value priorities? It is hypothesized that, for both sexes, the importance of benevolence, universalism, stimulation, hedonism, and self-direction values increases with greater gender equality, whereas the importance of power, achievement, security, and tradition values decreases. Of particular relevance to the present study, increased gender equality should also permit both sexes to pursue more freely the values they inherently care about more. Drawing on ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
229
3
16

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(272 citation statements)
references
References 38 publications
24
229
3
16
Order By: Relevance
“…Some studies have concluded that sustainability values play an important role in certain situations whenever they are stimulated by a set of compassionate combinations, and these comprised values have a positive relationship when coupled with pro-environmental behavior [43][44][45]. Therefore, this study proposed the following hypothesis.…”
Section: Sustainability Valuementioning
confidence: 97%
See 1 more Smart Citation
“…Some studies have concluded that sustainability values play an important role in certain situations whenever they are stimulated by a set of compassionate combinations, and these comprised values have a positive relationship when coupled with pro-environmental behavior [43][44][45]. Therefore, this study proposed the following hypothesis.…”
Section: Sustainability Valuementioning
confidence: 97%
“…The SV indicate certain fundamental values to be essential for the promotion of international relations [43][44][45]. Second, pro-social models motivated from self-interest intention provide better liability for personal sustainable traveling behavioral intention.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Inglehart explicitly states no value differences between men and women. Schwartz, by contrast, follows theories of gender differences in assuming that men attribute higher importance to instrumental values such as power or achievement, as well as stimulation, hedonism, or self-direction values, and lower importance to benevolence and universalism values (Schwartz, 2006Schwartz and Rubel, 2005;Schwartz and Rubel-Lifschitz, 2009;Meuleman et al, in press). Political Interest.…”
Section: The Impact Of Social-structural Variables On Valuesmentioning
confidence: 99%
“…Aunque no abundan las investigaciones sobre los correlatos de valor de los roles sexuales (Schwartz y Rubel, 2009), algunos estudios como el realizado por Prince-Gibson y Schwartz (1998) muestran que los varones priorizan valores instrumentales de poder y logro, mientras que las mujeres se orientan a valores de relación. Schwartz y Rubel (2005) encontraron, con pequeñas diferencias, que los hombres atribuyen de manera consistente mayor importancia que las mujeres a los valores poder, estimulación, hedonismo, logro y autodirección; y lo contrario ocurre con los valores benevolencia y universalismo, y menos consistente para el valor seguridad.…”
Section: Figura 1 Modelo Teórico Deunclassified